Nilai-Nilai Profetik Dalam Pendidikan Islam: Analisis Konsep Tarbiyah Qur’aniyyah Dalam Tafsir Al-Azhar Karya Buya Hamka - Mulyani, Sri; Yusuf, Enjang Burhanudin (CV. ITTC INDONESIA, 2025)
This article examines prophetic values in Islamic education through an analysis of the concept of tarbiyah Qur’aniyyah in Buya Hamka’s Tafsir Al-Azhar. The study aims to identify and analyze the dimensions of humanization, liberation, and transcendence reflected in Hamka’s interpretation of educational verses, particularly QS. Luqman: 13–19, QS. Al-‘Alaq: 1–5, and QS. Al-Ahzab: 21. This research employs a qualitative library approach using thematic Qur’anic interpretation (maudhu‘i) and content analysis of the tafsir text. The findings indicate that tarbiyah Qur’aniyyah in Tafsir Al-Azhar emphasizes the dignity of humanity through moral and ethical formation, the liberation of human beings from ignorance through literacy and knowledge development, and the strengthening of a transcendental orientation as the foundation of education. These findings highlight Islamic education as a holistic and integrative process rooted in Qur’anic values